2008
DOI: 10.3238/arztebl.2008.0413
|View full text |Cite
|
Sign up to set email alerts
|

The Children of Mentally Ill Parents

Abstract: Preventive measures for children of mentally ill parents urgently need improvement. In this article, positively evaluated programs of preventive measures are discussed. Essential prerequisites for success include appropriate, specialized treatment of the parental illness, psychoeducative measures, and special support (e.g. self-help groups) as indicated by the family's particular needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
53
0
16

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(72 citation statements)
references
References 10 publications
3
53
0
16
Order By: Relevance
“…Available evidence substantiates the model suggesting that parental distress is associated with increased probability of youth developing mental health problems (18,(27)(28)(29). Moreover, according to the Family Stress Model, the negative intergenerational impact on well-being is affected by strain in the parent-child relationship (30,31).…”
Section: Introductionmentioning
confidence: 83%
“…Available evidence substantiates the model suggesting that parental distress is associated with increased probability of youth developing mental health problems (18,(27)(28)(29). Moreover, according to the Family Stress Model, the negative intergenerational impact on well-being is affected by strain in the parent-child relationship (30,31).…”
Section: Introductionmentioning
confidence: 83%
“…Mattejat and Remschmidt (2008), based on the selective literature review, suggested several mechanisms mainly focused on the factors related to the parent-child relationship. For instance, depression may result in alteration of parental behaviours decreasing the quality of parenting.…”
Section: Link Between Parental and Offspring Depressionmentioning
confidence: 99%
“…These alterations may take a different form depending on the developmental stage of the child. For example, children in the kindergarten and elementary school years may be affected by reduced verbal communication or mother's difficulty to control children's behaviour and boundaries (Mattejat and Remschmidt 2008). Whereas older children and young people may be forced to take over tasks and responsibilities of their parents (Bparentification^), which leads to attenuated rolemodel function of the parents (Mattejat and Remschmidt 2008).…”
Section: Link Between Parental and Offspring Depressionmentioning
confidence: 99%
See 2 more Smart Citations